Hydrogeochemical and isotopic investigation of the Kolan geothermal field, southeastern Turkey - Okan, ÖÖ; Çetindag, B (Springer, 2005)
The Kolan geothermal field is located 24 km northwest of the Karakoc, an area of Elazig. city in southeastern Turkey. The Keban crystallized limestone of Permo-Carboniferous age is the oldest unit in the area. This unit is overlain by the middle-upper Eocene Kirkgec, it formation consisting of conglomerate, sandstone, limestone and marl alternations. The youngest unit in the area is the Upper Miocene-Lower Pliocene Karabakir formation consisting of basalt, andesite and tuffs. Thermal Springs in the Kolan field issue along two major fault zones. The temperature of the hot springs is between 38 degrees C and 45 degrees C. Thermal waters in the area are heated by the geothermal gradient. The waters are classified as hot'' or very hot'' and as brackish'' waters. On the basis of International Association of Hydrogeologists Classification (IAH), waters are grouped as Ca - Na- HCO3 - CO2-bearing thermal and mineral waters''. Chemical analyses indicate a chemical composition of Ca>(Na+ K)> Mg HCO3> SO4> Cl. Saturation calculations reveal that the waters are oversaturated with respect to calcite, dolomite and aragonite while undersaturated with respect to gypsum, anhydrite and halite minerals. On the basis of delta O-18, delta H-2 and H-3 isotope data, Kolan waters are of meteoric origin, recharged from high elevations and then circulated deeply.
Keywords: Kolan; geothermal; isotope; geothermometer; Turkey